1989
DOI: 10.1080/01652176.1989.9694201
|View full text |Cite
|
Sign up to set email alerts
|

A method for bronchoalveolar lavage in live pigs

Abstract: SUMMARY In order to isolate porcine alveolar macrophages and to quantitatively study the components of recovered lung fluid, a bronchoalveolar lavage technique in living pigs was developed. Lung lavage was performed after introducing a catheter through the mouth via the trachea in the diaphragmatical lobe. Thirty ml of phosphate-buffered saline (PBS) was introduced into the lung and the fluid was aspirated after one minute. Following this, another 15 ml of PBS was introduced into the lung and aspirated after o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
26
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 13 publications
(7 reference statements)
1
26
0
Order By: Relevance
“…The findings in the low health status pigs are in agreement with those of others who have reported that conventionally raised pigs have a lower percentage of AMs and higher percentages of lymphocytes and neutrophils in BAL fluid than specific-pathogen-free or germ-free pigs. 8,24 Conventionally raised pigs are exposed to a variety of antigenic stimuli, including pathogenic microorganisms, which are responsible for the increased percentages of neutrophils and lymphocytes. 1,9,18,20 In contrast with BAL data, hematology results of the high health status pigs were not influenced much by age and were similar to previously reported values.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings in the low health status pigs are in agreement with those of others who have reported that conventionally raised pigs have a lower percentage of AMs and higher percentages of lymphocytes and neutrophils in BAL fluid than specific-pathogen-free or germ-free pigs. 8,24 Conventionally raised pigs are exposed to a variety of antigenic stimuli, including pathogenic microorganisms, which are responsible for the increased percentages of neutrophils and lymphocytes. 1,9,18,20 In contrast with BAL data, hematology results of the high health status pigs were not influenced much by age and were similar to previously reported values.…”
Section: Discussionmentioning
confidence: 99%
“…This is in agreement with findings by others. 4,18,24 A third BAL was done at necropsy after removing the lung from the chest cavity. The BALs were done at 2.5-week intervals, which would allow enough time for resolution of any mild inflammatory response.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bronchoalveolar lavage fluid (BALF) was collected from five healthy 12-to 14-week-old Yorkshire-Landrace pigs by using standard veterinary procedures (52). All animal use protocols were approved by the Michigan State University Institutional Animal Care and Use Committee.…”
Section: Methodsmentioning
confidence: 99%
“…The volume of pulmonary epithelial lining fluid (ELF) in the recovered BALF was calculated both by measurement of the concentration of methylene blue in the BALF (3,52) and by using urea as a marker of dilution (39). Concentration of free amino acids and of urea in the BALF were measured by physiological amino acid analysis on a Hitachi I-8800 amino acid analyzer (Hitachi High Technologies America, Pleasanton, CA) (45) at the Michigan State University Macromolecular Structure Facility and compared to the concentration of urea in a plasma sample collected immediately prior to the lavage procedure.…”
Section: Methodsmentioning
confidence: 99%